2018
DOI: 10.1007/s00421-018-3938-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced trunk fatigue decreases double poling performance in well-trained cross-country skiers

Abstract: In well-trained cross-country skiers, exercise-induced trunk fatigue led to a substantial decrease in DP performance, caused by both decreased work per cycle and cycle rate and accompanied by reduced aerobic power. Hence, improved fatigue resistance of the trunk may therefore be of importance for high-intensity DP in cross-country skiing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Behavioral observations propose that exercise and brain function interact in a dose-response relationship, assigning the most beneficial effect on brain function to moderate-to high-intensity exercise (Herold et al 2019). In line with that, exhaustive exercise is associated with loss of distinct brain function, for instance, expressed by altered kinematics in cyclic motor tasks (Bassan et al 2015;Bucher et al 2018;Zory et al 2009). Consequently, the analysis of modulations of regional brain activity does not reflect this intensity-dependent pattern.…”
Section: Power Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral observations propose that exercise and brain function interact in a dose-response relationship, assigning the most beneficial effect on brain function to moderate-to high-intensity exercise (Herold et al 2019). In line with that, exhaustive exercise is associated with loss of distinct brain function, for instance, expressed by altered kinematics in cyclic motor tasks (Bassan et al 2015;Bucher et al 2018;Zory et al 2009). Consequently, the analysis of modulations of regional brain activity does not reflect this intensity-dependent pattern.…”
Section: Power Analysismentioning
confidence: 99%
“…Taken together, monitoring RSN efficiency by means of graph theory might help to better understand exerciseinduced modulations of human behavior. With regard to sport and exercise, the observed loss of RSN efficiency may serve to explain performance decrements during or after exhaustive exercise bouts (Bassan et al 2015;Bucher et al 2018;Zory et al 2009). Graph measures obtained from athletes during rest may therefore reveal complementary information on an athlete's readiness to perform motor coordination tasks, displaying the brains responsiveness to external stimuli (Raichle 2011).…”
Section: Brain Mechanisms Underlying Modulations Of Brain Networkmentioning
confidence: 99%
“…Nevertheless, numerous studies have reported that fatigue elicited by physical training translates into worsened sport performance. For instance, cross-country skiers had decreased double poling performance after a 25 min trunk fatiguing exercise sequence, compared with a 25 min rest [16], and fatigued ballet dancers exhibited impaired movement control, which may increase the risk of injury [17]. Interestingly, impaired performance appeared to be associated with not only physical and muscular fatigue, but also mental fatigue.…”
Section: Fatigue Lack Of Energy and Lower Physical And Cognitive Permentioning
confidence: 99%
“…Line of identity is shown as a dashed line. From Sandbakk et al (2014, 2016a), Skattebo et al (2016, 2019), Hegge et al (2015), Fabre et al (2010), Vandbakk et al (2017), Holmberg and Nilsson (2008), Borve et al (2017), Carlsson et al (2014, 2016), Bucher et al (2018), Sagelv et al (2018), Holmberg et al (2007), Bojsen-Moller et al (2010), Losnegard et al (2014), Bjorklund et al (2015), Nilsson et al (2004b), Rud et al (2014), Stadheim et al (2013, 2014) and Hoff et al (2002)…”
Section: Introductionmentioning
confidence: 99%